Ganzenbord met tekst: "In de grote KAB bouwt vader aan jouw toekomst mee", ter ere van 400.000ste lid (1956)
Ganzenbord met tekst: "In de grote KAB bouwt vader aan jouw toekomst mee", ter ere van 400.000ste lid.